Unveiling Egypt's cultural and educational horizons: Insights from the writings of Rifa’a Rafi’ al-Tahtawi, Taha Hussein, and Suliman Huzzyen - Ead, Hamed A.; Nuryana, Zalik (Research and Social Study Institute, 2024)
This study examines the works of three influential Egyptian intellectuals, Rifa'a Rafi' al-Tahtawi, Taha Hussein, and Suliman Huzzyen, to provide a comprehensive analysis of the future of culture and education in Egypt. The study delves into the writings of the selected intellectuals to shed light on their observations regarding the current political climate in Egypt. It also explores the challenges and opportunities facing Egypt's education system and cultural sphere. The article contributes to the ongoing discourse on the role of culture and education in Egypt's social and economic revolutions, identifying potential areas for future development and improvement. Egypt's cultural and educational landscape holds the key to its future progress and prosperity, making this study a valuable contribution to the understanding of the country's development.